Isolation of three genera of microorganisms in lahar-laden soils of Sta. Rita, Pampanga, Philippines through the 16s rRNA gene sequence analysis - Israel M. Guanzon; Maria Luisa T. Mason; Purisima P. Juico; Fernan T. Fiegalan (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2023)
A lahar-laden soil is described as marginal soil due to its poor physicochemical and biological properties and is hypothesised to have low biodiversity of soil microbes that would help support plant growth. Thus, the study aimed to assess the presence of soil microorganisms in lahar-laden soils in Sta. Rita, Pampanga, with their ability as beneficial microbes for crop production. Vigna radiata was used as the trap crop and grown for a maximum of 35 days in a microcosm experiment where all variables were similar except for the location of the sampling site. Through the sequence analysis of the 16S rRNA gene, five representative isolates revealed close resemblance to the genus Bradyrhizobium and Rhizobium, while the others were classified as non-rhizobial endophytes, namely, Pseudomonas, Agrobacterium, and Leifsonia. These results indicate that the lahar-laden soils in the sampling site harbour some agronomically-important genera of microorganisms. Surprisingly, this is the first time that the species Leifsonia xyli was identified and isolated in acidic lahar-laden soil. In contrast, it is hypothesised that the presence of L.xyli in this study might be attributed to the acidic soil pH, leading to the suppression of rhizobia in root nodules.